EFFECTIVENESS AND EFFICIENCY OF BUDGET REALIZATION'S LOCAL GOVERNMENT BEFORE AND DURING PANDEMIC: A CASE STUDY - Puspita Dewi Wulaningrum; Dina Fahma Sari; Parwoto Parwoto; Dinda Dewi Novitasari (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This purpose of study is to analyze the comparison of the performance of financial statements by taking into account the level of efficiency, and the effectiveness of the allocation of funds to assess budget accountability. The object of this research is the Regional Development Planning Agency of Magelang Regency and Yogyakarta City with the main data source being the 2018 to 2021 Budget Realization Report. This study uses a quantitative descriptive method with secondary and primary data types. Analysis of the data using the formula of efficiency and effectiveness. The analysis results from the calculations show that the percentage level of effectiveness of Magelang Regency before the pandemic (2018-2019) and during the pandemic (2020-2021) is in the effective level. The percentage level of the effectiveness of the City of Yogyakarta before the pandemic (2018-2019) and during the pandemic (2020-2021), which is in the effective percentage. The percentage level of efficiency in Magelang Regency before the pandemic (2018-2019) was in the less efficient percentage. Meanwhile, during the pandemic (2020-2021) it was in the efficient percentage and overall, it was in the fairly efficient category. The percentage level of efficiency of the City of Yogyakarta before the pandemic (2018-2019) and during the pandemic (2020-2021) was in the efficient percentage.